THE ROLE OF VOCATIONAL-ORIENTED COMUNICATIVE COMPETENCIES OF CADETS - Khatamova Gulbakhor Abdumomin kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article delves into the pivotal role played by vocational- oriented communicative competencies among cadets. The study explores the importance of effective communication in vocational settings, particularly within military training. Drawing upon literature analysis and empirical research, the article investigates the methods employed to enhance communicative skills among cadets, presents the results of such interventions, and engages in a comprehensive discussion on their implications. The conclusions drawn shed light on the broader implications for military training programs, emphasizing the need for a nuanced understanding of communicative competencies in vocational contexts.